Rating the certainty in evidence in the absence of a single estimate of effect. Issue 3 (20th March 2017) - Murad, M Hassan; Mustafa, Reem A; Schünemann, Holger J; Sultan, Shahnaz; Santesso, Nancy
Abstract : When studies measure or report outcomes differently, it may not be feasible to pool data across studies to generate a single effect estimate (ie, perform meta-analysis). Instead, only a narrative summary of the effect across different studies might be available. Regardless of whether a single pooled effect estimate is generated or whether data are summarised narratively, decision makers need to know the certainty in the evidence in order to make informed decisions. In this guide, we illustrate how to apply the constructs of the GRADE (Grading of Recommendation, Assessment, Development and Evaluation) approach to assess the certainty in evidence when a meta-analysis has not been performed and data were summarised narratively.